Pengaruh Pemberian Virgin Coconut Oil (VCO) dan Olive Oil terhadap Mikroanatomi Ren Tikus Putih (Rattus norvegicus) - Nurasri, Riani; Wachidah Yuniwarti, Enny Yusuf; Djaelani, M Anwar (Bioma : Berkala Ilmiah Biologi, 2018)
Virgin Coconut Oil (VCO) and olive oil have been widely applied in the field of health. Saturated fatty acid content of VCO dominates the total fatty acid content of about 85%. Olive oil contains a lot of oleic acid, which is one type of unsaturated fatty acid (mono-unsaturated fatty acid). This study aimed to analyze the kidney microanatomy rat (Rattus norvegicus) after supplementation with VCO and olive oil in the feed. This study used 25 rats were divided into five treatment groups, P1 was the control group, P2 was a group with VCO 5 mL / kg feed, P3 was a group with VCO 10 mL / kg of feed, P4 was a group with olive oil 5 mL / kg feed and was a group with olive oil 10 mL / kg of feed. The results of ren weight and diameter rat glomerular analyzed using analysis of variance (ANOVA). Research design used was completely randomized design with five treatments and five replication. Results of studies on weight ren showed no significant difference between treatments P2, P3, P4 and P5 to the control (P1). The results of the glomerular diameterÂ  shows there is significantly difference between the diameter of the glomerulous treatment P2 and P3 with control (P1), while in treatment P4 and P5 are not significantly different from the control so that it can be concluded that the administration of the VCO and olive oil at various concentrations do not give rise to different responses to weight ren. Olive oil does not increases glomerular diameter white mice, while VCO at a dose of 5 mL / kg feed and 10 mL / kg of feed can increased glomerular diameter mice.Â Keywords: ren weight, glomerular diameter, Virgin Coconut Oil (VCO), olive oil.